Effect of growth stages and storage conditions on the content of active constituents and biological activities of turmeric and zedoary rhizomes - Siriwan Wongvarodom (Prince of Songkla University, 2004)
Thesis (M. Phram.,Pharmatical Sciences) - - Prince of Songkla University, 2004